Development and application of a relative soil water content – transpiration efficiency curve for screening high water use efficiency wheat cultivars - Qiao, Yunzhou; Li, Dongxiao; Qiao, Wenjun; Li, Yongpeng; Yang, Hong; Liu, Wenwen; Liu, Mengyu; Zhang, Xiying; Dong, Baodi (Frontiers in Plant Science, 2022)
Drought is the most serious abiotic stress factor limiting wheat production in arid and semiarid regions. Improving water use efficiency (WUE) has been proven to be a prosperous way to produce more grain in drought-prone areas. Transpiration efficiency (TE) has been proposed as a criterion for screening cultivars with high WUE. This study quantifies the relations of TE to relative soil water content (RSWC) gradients using pot experiments and evaluates the capability of the relations of TE-RSWC on assessing the cultivar performance in yield and WUE grown in the field. Twelve winter wheat cultivars were grown at 6 RSWC, 12.1%, 24.2%, 36.3%, 48.4%, 60.5%, and 72.6% of field capacity (FC = 24.8 g/g) for 40 days in tightly sealed pots in which soil evaporation was mostly prevented. The results showed that TE decreased power functionally following the increase in RSWC for all cultivars. The relationship could be described as TE = TE FC × (RSWC) b and is named the TE–RSWC curve. The curves could be divided into an orderly area where the rank of cultivars was stable when RSWC ≤ 12.1% or RSWC ≥ 72.6% and a disorderly area where the rank was unstable when 12.1% < RSWC < 72.6% when compared among cultivars. To assess the consistency of pot TE to field yield and WUE, the same 12 varieties were grown under two water levels, rainfed and two irrigations (75 mm at the jointing stage and the flowering stage, respectively). TE FC was found to be positively related to field yield and WUE independent of irrigation among the 12 cultivars. TE measured near the wilting point was negatively related to field yield and WUE. The results indicated that TE FC could be used as a surrogate for screening high-yield and high-WUE cultivars. The consistency and inconsistency can be attributed to the orderly area and disorderly area of the TE–RSWC curves.